Resistência, rigidez e conductividade hidráulica de misturas compactas submetidas à percolação ácida - Silva, Franciele Noll da (2015)
The inadequate disposal of industrial and mining solid wastes have become a potential issue, especially because of the negative impacts on the environment and human health. This occurs mainly through the contamination of subsurface soil and groundwater by wastewaters, which are often of acidic constitution. To prevent situations like this, the study and improvement of efficient containment techniques for wastes generated in potentially polluting activities has become necessary and opportune. In this way, this work was aimed to investigate the mechanical and hydraulic behavior of two different compacted soils, with and without the addition of Portland cement (0 and 2%), submitted to the action of a sulfuric acid solution (2% volume concentration) and to a constant static vertical load (280 kN/m2), aiming at its prospective application as containment barrier. The experimental program comprised a few permeability tests, performed in an instrumented rigid-wall permeameter, during which the variations in hydraulic conductivity, shear deformation modulus, and settlement were measured and analyzed. In addition, for the specimens percolated with the acidic solution, the split tensile strength was also determined. The results showed that the hydraulic conductivity increased with cement addition and decreased with the acidic percolation. Regarding the mechanical behavior, the acidic percolation caused, almost instantaneously, an increase in settlement rate and a reduction in stiffness, although the trend of stabilization observed afterwards, until the end of the tests.